On the meaning of Intensifiers - Constantinou, Harris (Proceedings of the Amsterdam Colloquium, 2013)
The intensifier, or emphatic reflexive, is a stressed anaphorically dependent element, exemplified by himself in John himself built this house. Depending on its distribution, the intensifier may take up to three radically different interpretations: adnominal, exclusive and inclusive. I claim that the common denominator of the three readings is the centrality effect imposed on the antecedent. The analysis departs from Eckardt (2001) and suggests that while the adnominal interpretation denotes the identity function ID operating on the domain of individuals De (i.e. ID (x)), the inclusive and exclusive respectively constitute clausal and manner adverbial variations of ID (x), that is, ID (e, x).